Explicit R-symmetry breaking and metastable vacua - Marqués, Diego (2008)
We consider O'Raifeartaigh-like models with explicit R-symmetry breaking and analyze the vacuum landscape. Taking such models as candidates for the hidden sector, we analyze the gauge mediation of the supersymmetry breaking, focusing on the effects produced by R-symmetry breaking. First, we construct families of non-R-symmetric models containing only singlet chiral superfields, and determine the conditions under which SUSY vacua, runaway directions and (longlived) metastable vacua exist. We then extend the results to the case in which some of the chiral fields are in the 5⊕5 representation of SU(5). Gauging this symmetry, we compute soft masses for gauginos and sfermions, and analyze several issues such as doublet/triplet splitting, unification of coupling constants and CP violation phases.